TO THE QUESTION OF THE FORMATION OF THE CONCEPT OF THE PERSONNEL POLICY OF PUBLIC AUTHORITIES - S. Zudenkova (Вестник университета)
Governance improving assumes the further development of the Civil Service Institute. Increase of the prestige of the State civil service can not be realized without using and combining various human resource technologies, which in turn places high requirements to the personnel policy, explains the need for its formalization as the concept of personnel policy. The analysis revealed, that in Russian Federation there is virtually nonexistent concept of personnel policy in State authorities, identified the main challenges of designing and implementing the concept of personnel policy.